EFFECT OF SALINITY AND SILICATE ON ICE ALGAL GROWTH IN SAROMA KO LAGOON, HOKKAIDO, JAPAN (EXTENDED ABSTRACT) (16th Symposium on Polar Biology) - タグチ, サトル; / シラサワ, クニオ; TAGUCHI, Satoru; SMITH, Ralph E. H.; SHIRASAWA, Kunio (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper